The Effect of Zakat Literacy, Religiosity, and Income on the Decision to Pay Agricultural Zakat - Johan Arifin; Ferry Khusnul Mubarok; Nasrul Fahmi Zaki Fuadi (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
Awareness of paying agricultural zakat is still not significantly developed because many people, especially farmers, do not understand the practicalities of paying their agricultural zakat. This study aims to determine the effect of Zakat Literacy, Religiosity, and Farmer's Income on the Decision to Pay Agricultural Zakat. This study uses a quantitative method using primary data obtained through a questionnaire. The sampling technique uses purposive. The data analysis technique uses multiple linear regression using SPSS Version 22 software. The results of the analysis and hypothesis testing show that zakat literacy has a positive effect on the decision to pay agricultural zakat. The income variable also positively and significantly affects the decision to pay zakat. Meanwhile, the religiosity variable does not affect the decision to pay agricultural zakat. Based on these results, it is necessary to socialize and improve a more massive pick-up strategy to optimize agricultural zakat.